ANTISIPASI SATUAN KOMANDO KEWILAYAHAN TNI AD MENGHADAPI ERA BONUS DEMOGRAFI MENUJU INDONESIA EMAS 2045 - Tatang Sulaiman; Agus Subagyo (Universitas Jenderal Ahmad Yani, 2024)
This research aims to analyze the anticipation of the regional command units of the Indonesian National Army in facing the era of the demographic bonus towards a Golden Indonesia 2045. As one of the components of the nation, the Indonesian National Army seeks to assist the government in utilizing the demographic bonus so that it becomes a demographic blessing and not a disaster demographics. The theoretical conceptual framework used is the concept of territorial development. The research method used is a qualitative method and data collection techniques in the form of observation, interviews and documentation. The results of this research show that the anticipation of the territorial command units of the national army in facing the demographic bonus is carried out by carrying out territorial development functions (geographic development, demographics, social conditions) and territorial development methods (social communication, regional resilience development, TNI service), as well as ideas innovation in the form of territorial development that focuses on education, health and economic aspects.